European Fiscal Union: What Is It? Does It Work? And Are There Really 'No Alternatives'? - Clemens Fuest; Andreas Peichl (Institute for the Study of Labor (IZA), 2012)
The view is widespread that there are just two options for the future of the Eurozone either it is complemented by a fiscal union, or it will fall apart. In this paper, we discuss five possible elements of a fiscal union, of which three are in the centre of the current debate on fiscal union in the Eurozone. Second, we argue that the fiscal union will only work if political integration in Europe goes significantly beyond the current state of affairs. Third, we suggest an alternative approach, which places less emphasis on centralised fiscal policy coordination and focuses on financial sector reform, decentralised responsibility for government debt and sovereign debt restructurings in the case of fiscal crises.
Keywords: E62; H77; H87; 330; ESM; Euro; EMU; EU; Fiscal Union; Finanzverfassung; Finanzpolitik; Eurozone; Internationale Wirtschaftspolitik; Haushaltskonsolidierung; Eurozone